KAJIAN KEHIDUPAN SOSIAL EKONOMI MASYARAKAT TRANSMIGRASI DI DESA JAIRAN JAYA KABUPATEN KETAPANAG - Beku, Hilaria Arbaleta; Aminuyati, Aminuyati; Okianna, Okianna (Universitas Tanjungpura, 2024)
The purpose of this study was to determine the socio-economic life of the transmigration community in Jairan Jaya Village, Ketapang Regency based on their level of education, housing conditions, health level, income level, type of work.. This study uses a qualitative approach to the type of phenomenological research. Collecting data using interview techniques, observation, and documentation as well as using techniques snowball sampling in determining informants. The results showed that the education level of the transmigration community was low because the majority of the transmigration community had graduated from elementary, middle and high school, then the housing conditions of the transmigration community showed a change because the transmigration community had settled in private homes that were built by themselves. then the health level of the transmigration community the high class because change occurs in public awareness about clean and healthy living behavior as well as the existence of health services and health counseling. Then the income level of the transmigration community is relatively high and has experienced changes from the beginning of their arrival to the present. Based on the type of work, it shows that the majority of transmigration people work as oil palm farmers from the beginning until now.